PENGARUH SUKU BUNGA, TINGKAT INFLASI, INDEKS HARGA SAHAM GABUNGAN, DAN PERTUMBUHAN JUMLAH UANG BEREDAR TERHADAP TINGKAT PENGEMBALIAN REKSADANA SAHAM TAHUN 2014-2017 - Muhamad Reza Noviandi; Jeni Reza Noviandi; M. Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT The purpose of this study is: 1) To analyze the effect of the interest rate of Indonesian bank certificates on the return rate of stock funds. 2) To analyze the effect of the inflation rate on the return rate of the stock fund. 3) To analyze the effect of the composite stock price index on the return rate of the stock fund. 4) To analyze the effect of the growth of the money supply on the rate of return of stock funds. This research uses quantitative research method with time series data form. Sampling in this study using the method of purposive sampling with a sample of 48 stock mutual funds.The results of this study indicate that: 1) Interest rates of certificates of Indonesian banks have a positive and significant effect on the return rate of mutual fund shares. 2) Inflation rate has a positive and significant effect on return rate of stock fund. 3) The composite stock price index has a positive and significant effect on stock returns. 4) Growth in the money supply has a positive and significant effect on the rate of return on equity funds. This shows that the rate of return on equity funds listed in BAPEPAM and recorded in the OJK (financial services authority) is influenced by the interest rate of Indonesian bank certificates, inflation rates, composite stock price indexes, and growth in the money supply. Keywords: Stock Mutual Fund Return Rate, Bank Indonesia Certificates Interest Rate, Inflation Rate, Composite Stock Price Index, Growth in Amount of Money Supply.